2001
DOI: 10.1097/00124784-200107030-00007
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Infant Mortality

Abstract: This article presents the multifaceted efforts of Syracuse Healthy Start, a federally funded initiative of the Onondaga County Health Department and over 20 partnering agencies to reduce racial and ethnic disparities in infant mortality. The analyses presented in this article demonstrate that many women--Caucasian, African American, and Hispanic--have serious risks for low birth weight and infant death. In many cases, multiple, simultaneous risks complicate a pregnant woman's situation and in other cases the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…One study of pregnant CHC users, in fact, found that enabling services were associated with more timely receipt of perinatal care (Lewis-Idema 2002). Moreover, CHCs coordinate with national and local initiatives such as the Women, Infants, and Children (WIC) program and Healthy Start, which have been linked with better infant outcomes (Gregory and de Jesus 2003;Kowaleski-Jones and Duncan 2002;Lane et al 2001;Moss and Carver 1998).…”
Section: Discussionmentioning
confidence: 99%
“…One study of pregnant CHC users, in fact, found that enabling services were associated with more timely receipt of perinatal care (Lewis-Idema 2002). Moreover, CHCs coordinate with national and local initiatives such as the Women, Infants, and Children (WIC) program and Healthy Start, which have been linked with better infant outcomes (Gregory and de Jesus 2003;Kowaleski-Jones and Duncan 2002;Lane et al 2001;Moss and Carver 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis used data from the Syracuse Healthy Start (SHS) participants' database [30], which monitors the receipt of preventive care of pregnant women of all ages. SHS is an infant mortality prevention project of the Onondaga County Health Department (OCHD) that has been funded by the Health Resources and Services Administration since 1997.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of psycho pathology African Americans are known to suffer disproportionately high neigh bourhood and social stressors (HambrickDixon, 2002;Schulz et al, 2000). African Americans in the United States also have the highest risk for low birth weight deliv eries, short gestation births and infant mortality (Lane et al, 2001). This is especially true for African Americans in Louisiana (Curtis and Leitner, 2006).…”
Section: African-american Neighbourhoodsmentioning
confidence: 99%